2012
DOI: 10.1111/j.2042-3306.2012.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgical technique for unilateral orchiectomy on subsequent testicular function inMiniatureHorse stallions

Abstract: SummaryReasons for performing study: Management decisions on unilateral orchiectomy are often influenced by the potential for post operative return to successful breeding. The effects of 2 surgical methods (first intention [FI] vs. second intention [SI] incision healing) for unilateral orchiectomy on resulting semen quality and scrotal temperature were evaluated. Objective: To evaluate the effects of 2 surgical unilateral orchiectomy techniques on scrotal healing, size of the remaining testis and post operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…It is unclear how soon after orchiectomy a stallion can return to breeding service due to the local inflammation and heat produced by the surgical procedure; therefore, it is often assumed that a minimum of one spermatogenic cycle (w60 days) should be allowed for sperm quality to return to pre-UO levels. In a previous complementary study, sperm quality (i.e., motility, morphology, viability) did not change at 14, 30, or 60 days after UO [16], compared to pre-UO levels. These results suggested that the degree of scrotal inflammation surrounding the surgical site after UO represented a "mild" testis stress that was not sufficient to elicit a decline in traditional sperm quality measures; however, DNA quality was not evaluated.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…It is unclear how soon after orchiectomy a stallion can return to breeding service due to the local inflammation and heat produced by the surgical procedure; therefore, it is often assumed that a minimum of one spermatogenic cycle (w60 days) should be allowed for sperm quality to return to pre-UO levels. In a previous complementary study, sperm quality (i.e., motility, morphology, viability) did not change at 14, 30, or 60 days after UO [16], compared to pre-UO levels. These results suggested that the degree of scrotal inflammation surrounding the surgical site after UO represented a "mild" testis stress that was not sufficient to elicit a decline in traditional sperm quality measures; however, DNA quality was not evaluated.…”
Section: Discussionmentioning
confidence: 75%
“…This present study compared the results of two DNA assays using the same ejaculates from a previous study [16] to determine whether a "mild" testis stress could be detected by either of the assays. It seems unlikely that DNA quality would be reduced in a model in which sperm motility, morphology, or viability were not affected; nevertheless, lower DNA quality was detected by both assays in the present study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…McCormick et al . investigated the effect of unilateral orchiectomy via parainguinal approach in Miniature Horse stallions and found that compensatory hypertrophy was evident by 30 days post operatively . Incisions were either surgically closed or left to heal by second intention; mean (± s.d.)…”
Section: Reproductionmentioning
confidence: 99%